ANALISIS PROSEDUR PENGUJIAN SUBTANTIF TERHADAP AKUN KAS DAN BANK PADA PT X OLEH KAP Drs. PAUL HADIWINATA, HIDAJAT, ARSONO, RETNO, PALILINGAN & REKAN (KAP PKF HADIWINATA) - Putri Aisyah (2022)
Substantive tests of cash and bank accounts are needed to identify fairness in disclosures and fairness in the statement of financial position. Interviews are a way for auditors to dig deeper into the records that clients usually do. The audit work paper is evidence of an auditor's examination, the nominal results of which have been examined will be disclosed to the client's financial statements. This substantive cash and bank test was carried out on one of the companies engaged in transformation consulting services that offers integrated services from strategy to digital business implementation. It is concluded that the results of this study are a process of substantive testing procedures for cash and bank balances carried out by the Public Accounting Firm PKF HADIWINATA which have been carried out in accordance with auditing standards applicable in Indonesia.